مدى توافر نظام تقدير ذاتي متكامل وفعّال في ظل قانون ضريبة الدخل رقم (24) لعام 2003 وتعديلاته في سورية (دراسة ميدانية على مديريات المال في الساحل السوري) - الضابط مدين إبراهيم (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف هذا البحث إلى التعرف على أحد أهم العوامل التي تسهم في تحسين الالتزام الضريبي بشكل عام، وهو تطبيق نظام التقدير الذاتي في الكثير من النظم الضريبية على المستوى الدولي، ومن بينها النظام الضريبي السوري. يركز هذا البحث على قياس مدى توافر نظام تقدير ذاتي بجميع مقوماته في ظل قانون ضريبة الدخل السوري رقم /24/ لعام 2003 وتعديلاته، ومدى فعاليته في عملية التطبيق. وقد أظهرت نتائج هذا البحث أن جزءاً من مقومات هذا النظام غير موجودة بالفعل، مما انعكس سلباً على الفعالية المطلوبة في أداء الوظائف وتحقيق الأهداف التي صمم أساساً من أجلها. وعليه، فقد أوصت الدراسة بضرورة إيجاد وتفعيل تلك المقومات ضمن مجموعة من العوامل البيئية الأخرى التي تعمل مع بعضها البعض لتحقيق الفعالية المطلوبة، وتحسين معدل الالتزام الضريبي. This research aims to identify one of the most important factors that contribute in improving of tax compliance in general, which is an implication of self-assessment system in a lot of tax systems at the international level, including the tax system in Syria. This research focuses on measuring the availability of a self-assessment system in all its components under the income tax law N.24 of 2003, and its amendments in Syria, and its effectiveness in the application process. The results of this research showed that part of the elements of this system does not exist already, which reflected negatively on the effectiveness required in the performance of the functions and achieve the goals that is mainly designed for. Accordingly, the study recommended the need to find and activate these ingredients within the range of other environmental factors that work with each other to achieve the desired effectiveness, and improve the rate of tax compliance.